Comparative study in the paradigm of art research and art creation - Sunarto, Bambang (Creativity Studies, 2023)
This article reveals the epistemology of the pillars of existence between art research and artistic creation. The main focus is to tell about the nature of the paradigm, especially the paradigm of research and artistic creation. This discussion is necessary because both have been present as art disciplines that have received wide attention in the academic world. This paper elaborates ideographically on the thoughts of researchers and artists comprehensively when researching and creating art. The aim is to improve epistemological literacy in learning the implementation of research and creating works of art with strong pillars of existence. Anyone concerned with research and art creation has significant potential to carry out academic tasks. Whoever they are, they need a pillar of existence as the basis for intellectual performance. This article describes the nature of the pillars of existence in art research activities and the nature of the pillars of existence in art creation activities. The elements of the two paradigms, the relationship between the pillars of existence, and the elements of the paradigm will receive great attention. This explanation has an important meaning, namely to foster regular reasoning in the development of the paradigm of researchers and art creators, as well as to stimulate the spirit to be accountable for their work academically for art researchers and creators.